Self-Organized Criticality in the Brain - Plenz, Dietmar; Ribeiro, Tiago L.; Miller, Stephanie R.; Kells, Patrick A.; Vakili, Ali; Capek, Elliott L. (Frontiers in Physics, 2021)
Self-organized criticality (SOC) refers to the ability of complex systems to evolve towards a second-order phase transition at which interactions between system components lead to scale-invariant events that are beneficial for system performance. For the last two decades, considerable experimental evidence has accumulated that the mammalian cortex with its diversity in cell types, interconnectivity, and plasticity might exhibit SOC. Here we review experimental findings of isolated, layered cortex preparations to self-organize towards four dynamical motifs presently identified in the intact cortex in vivo: up-states, oscillations, neuronal avalanches, and coherence potentials. During up-states, the synchronization observed for nested theta/gamma-oscillations embeds scale-invariant neuronal avalanches, which can be identified by robust power law scaling in avalanche sizes with a slope of -3/2 and a critical branching parameter of 1. This precise dynamical coordination, tracked in negative transients of the local field potential (nLFP) and spiking activity of pyramidal neurons using 2-photon imaging, emerges autonomously in superficial layers of organotypic cortex cultures and acute cortex slices, is homeostatically regulated, exhibits separation of time scales, and reveals unique size vs. quiet time dependencies. A subclass of avalanches, the coherence potentials, exhibits precise maintenance of the time course in propagated local synchrony. Avalanches emerge in superficial layers of cortex under conditions of strong external drive. The balance of excitation and inhibition (E/I), as well as neuromodulators such as dopamine, establish powerful control parameters for avalanche dynamics. This rich dynamical repertoire is not observed in dissociated cortex cultures, which lack the differentiation into cortical layers and exhibit a dynamical phenotype expected for a 1st order phase transition. The precise interactions between up-states, nested oscillations, and avalanches in superficial layers of cortex provide compelling evidence for SOC in the brain.